Knowledge and attitude towards Polycystic Ovarian Syndrome (PCOS) among Malaysian undergraduate female students - Doustjalali, Saeid Reza; Sabet, Negar Shafiei; BSD, Lubnah; EA, Rebecca; MA, Rufina; GA, Thed; Mohd Desa, Mohd Nasir (International Journal of Early Childhood Special Education, 2022)
Polycystic Ovarian Syndrome (PCOS) is a common reproductive endocrine disorder in women which usually affect adolescents’ girls and young women. Today, the prevalence of PCOS is increasing rapidly, while most young people are unaware of this condition. Globally, it affects 5% to 10% of women during their reproductive years. This can cause alterations in the menstrual cycle, infertility, obesity, extreme acne problems and other health problems. The aim of this study was to determine the knowledge and attitude towards PCOS among Malaysian undergraduate female students. Therefore, we believe that this study will give us an opportunity to increase the knowledge as well as to promote their attitude towards PCOS among Malaysian female undergraduate students. Henceforth, creating a positive impact on this problem. The sampling method that was used in this research was a cross-sectional study that was carried out by using a convenience sampling methodwhereby the responses of 120 female undergraduate students with 20 Malays, 20 Chinese and 20 Indians from both the medical and non-medical fields were collected through online platforms. The data was analysed by using SPSS. In our data, regarding comparison of the knowledge between female medical and non-medical undergraduate students about PCOS, questions 1,4,5,6,7,9,10,12 and 13 showed statistical significance with Pvalues less than <0.05 contrary to questions 2,3,8 and 11 which showed no significance as their P values were greater than >0.05. Moreover, regarding the comparison of attitude between medical and non-medical towards PCOS among undergraduate female students, the question 1, 2, 3, 6, and 7 showed statistically significant with the P-value of less than <0.05. Furthermore, for the question 4 and 5 the data showed that statistically not significant with the P-value of higher than >0.05. Therefore, in conclusion, our study revealed that majority of the female undergraduate medical students had more knowledge and a more positive attitude towards PCOS compared to non-medical female undergraduate students. Further research can be done using a bigger sample size as it would have yielded more accurate results and would have less error. Moreover, knowledge plays a great role in forming attitude. Therefore, by identifying where the lack of knowledge come from, we can improve the attitude of the individuals. In addition, health education programs can help them gain a better understanding of the subject.